A gatekeeper residue of ClpS1 from arabidopsis thaliana chloroplasts determines its affinity towards substrates of the bacterial N-end rule - Colombo, Clara V.; Mogk, Axel (Plant & cell physiology, 2018)
Abstract. Proteins that are to be eliminated must be proficiently recognized by proteolytic systems so that inadvertent elimination of useful proteins is avoid
Gesehen am 03.06.2019